The itsy bitsy snowman - Burton,Jeffrey (Little Simon, 2015)
A fun and playful seasonal twist on “The Itsy Bitsy Spider” makes this favorite nursery rhyme perfect for wintertime! The itsy bitsy snowman went sledding into town, looking at the snowflakes softly falling down. Out came his friends to lend a happy hand. And everything was perfect in his winter wonderland. Little ones will love this fresh winter spin on a classic nursery rhyme, as one little snowman sleds through a winter wonderland.